2020
DOI: 10.1161/circulationaha.119.043400
|View full text |Cite
|
Sign up to set email alerts
|

Preventive or Deferred Ablation of Ventricular Tachycardia in Patients With Ischemic Cardiomyopathy and Implantable Defibrillator (BERLIN VT)

Abstract: Background: Catheter ablation for ventricular tachycardia (VT) reduces the recurrence of VT in patients with implantable cardioverter-defibrillators (ICDs). The appropriate timing of VT ablation and its effects on mortality and heart failure progression remain a matter of debate. In patients with life-threatening arrhythmias necessitating ICD implantation, we compared outcomes of preventive VT ablation (undertaken before ICD implantation to prevent ICD shocks for VT) and deferred ablation after 3 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
93
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 32 publications
2
93
0
6
Order By: Relevance
“…14,15 As expected, all of these trials had methodological differences but the major approach studied is homogenous, considering the use of first-line VT ablation in each of them and a medication-based approach in the control groups. In terms of the control groups, AADs were used in 35% of patients in the VTACH study, 32% in SMS, and 33% in BERLIN VT; however, only beta-blockers were used in SMASH VT. 5,6,15,16 All control groups were medications based except in the BERLIN VT trial, where patients were randomized to receive ablation after the third appropriate ICD shock. 15 Ultimately, 10 patients (12%) received ablation in this group, which is perhaps one of the reasons the trial showed no benefit in the ablation groupo.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…14,15 As expected, all of these trials had methodological differences but the major approach studied is homogenous, considering the use of first-line VT ablation in each of them and a medication-based approach in the control groups. In terms of the control groups, AADs were used in 35% of patients in the VTACH study, 32% in SMS, and 33% in BERLIN VT; however, only beta-blockers were used in SMASH VT. 5,6,15,16 All control groups were medications based except in the BERLIN VT trial, where patients were randomized to receive ablation after the third appropriate ICD shock. 15 Ultimately, 10 patients (12%) received ablation in this group, which is perhaps one of the reasons the trial showed no benefit in the ablation groupo.…”
Section: Discussionmentioning
confidence: 77%
“…13 Four randomized controlled trials have assessed the impact of first-line VT catheter ablation in the setting of ICM. 5,6,14,15 SMASH VT and VTACH trials showed improved outcomes with first-line VT ablation in patients with ICM presenting with VT. 5,6 However, the SMS and the recently published BERLIN VT trial, showed opposite results. 14,15 As expected, all of these trials had methodological differences but the major approach studied is homogenous, considering the use of first-line VT ablation in each of them and a medication-based approach in the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite we have the benefit of a preventive ablation, which has been shown in two randomized trials ( VTACH 7 and SMASH VT trials 8 ) and also a multicenter registry, 9 the recent BERLIN VT study 10 did not reduce mortality or hospitalization for VT or worsening HF between the preventive (very early) and the deferred (early) ablation group 10 . Although the VTACH study showed that there was no benefit of catheter ablation in patients with a very low ejection fraction (LVEF, <20%), 7 the BERLIN trial in lower risk patients with relatively preserved ejection fraction (LVEF, 30‐50%) detected no benefit for hard clinical outcomes, but fewer ventricular arrhythmias (VA) and implantable cardioverter‐defibrillator (ICD) interventions 10 . But this was fully compensated by early hospitalizations after ablation for worsening HF, 10 as did in current study 1 .…”
mentioning
confidence: 99%
“…On the other side, it is clear and mandatory to intervene aggressively when an electrical storm occurs, although there is still a lack of clarity about triggering mechanism and role of electrical storm in accelerating mortality 11 . Therefore, the correct timing and selection of patients determine the success of VT ablation as a curative or palliative approach and a shift in our goal of VT ablation 2,10,12 . We should be able to define the optimal time when it is not too early or late to perform the ablation procedure.…”
mentioning
confidence: 99%